Determining the Generations of Women in Türkiye Who Gave Birth between 2001-2021 and Birth Propensity According to Generation - Müjde Aydoğdu (Coğrafya Dergisi)
Birth trends vary from country to country and can vary according to age, working conditions and educational conditions. Moreover, in recent years, it has been shown that the period in which a woman is born and her country’s status, political conditions and incentives to be able to affect the number of births as well as the age when they will give birth. This period, regarded as age generations affects the tendencies of individuals who were born during that time, causes them to behave similarly. This study examines the birth trends of Turkish women between 2001 and 2021, according to their age generation. These mothers are basically from four generations; the Baby Boomer Generation from 1946-1964, Generation X from 1965-1979, Generation Y from 1980-1999, Generation Z from 2000-2020. Between 2001 and 2021, 18.341.959 women from Generation Y born have become mothers, while 7.265.941 people from Generation X born have been mothers. At least in Generation Z, the Baby Explosion was followed by the mothers. Women born in Generation Y had more births by the age of 40, and after 40, the number began to decrease. While this view is valid for Gen X mothers, Baby Boom mothers have the opposite, and women have given birth after age 40.